BIOM-28. SERIAL PLASMA AND CSF CELL-FREE TUMOR DNA (cf-tDNA) TRACKING IN DIFFUSE MIDLINE GLIOMA PATIENTS UNDERGOING TREATMENT WITH ONC201. (12th November 2021) - Cantor, Evan; Wierzbicki, Kyle; Tarapore, Rohinton; Ravi, Karthik; Wadden, Jack; Babilla, Clarissa; Thomas, Chase; Cartaxo, Rodrigo; Yadav, Vivek Anand; Ravindran, Ramya; Bruzek, Amy K; Cummings, Jessica; et al.
Abstract: Diffuse midline glioma (DMG) with H3K27M mutation is a lethal childhood brain cancer, with limited means of monitoring beyond serial MRI scans. We conducted a multi-site Phase 1 trial of the imipridone ONC201 for children with H3K27M-mutant glioma (NCT03416530). Patients on Arm D of the trial (n=24) underwent serial lumbar puncture (baseline, 2 and 6-months) for cell-free tumor DNA (cf-tDNA) analysis at time of MRI. Additionally, patients on all arms of the trial at the University of Michigan underwent serial plasma collection. We collected a total of 96 plasma-samples and 53 CSF-samples from 29 patients. We performed ddPCR analysis of cf-tDNA samples and compared variant allele fraction (VAF) to radiographic change (maximal tumor area on MRI). For our H3F3A-mutated (K27M) patients, cf-tDNA was positive in 53/62 plasma samples (sensitivity 85.4%) and 28/29 CSF samples (sensitivity 96.5%) and overall specificity of 100%. There was no direct correlation between percent-change in tumor-area and plasma (p=0.47) or CSF VAF (p=0.89), implying that VAF provided information supplemental to radiographic assessments. "Spikes" in plasma cf-tDNA VAF (increase of ≥25%) co-occurred with progression in 2/9 (22%) cases and preceded progression in 5/9 cases (55%) by an average of 1.22 months. In CSF, spikes preceded progression in 4/6 cases (66%) by an average of 1.8 months. Two patients had increases in tumor-area with no increase in plasma VAF; both were later confirmed as pseudo-progressors, suggesting additional potential utility of cf-tDNA VAF monitoring. A 14yo male with spinal cord glioma received concurrent bevacizumab with ONC201, which resulted in a decrease in tumor area but continued increase in plasma VAF, predicting radiologic progression at the next time. In summary, we present data which suggests monitoring serial CSF/plasma H3K27M tDNA is a promising clinical tool. Changes in cf-tDNAVAF over time appear to correlate with response, predict progression, and differentiate pseudo-progression.